Levels of Tumor Necrosis Factor-α (TNF-α) and Transforming Growth Factor-β1 (TGF-β1) in Gingival Crevicular Fluid During Canine Retraction Using Elastic Chain and Closed Coil Spring - Sri Suparwitri; Wahyu Hidayat; H. Hendrawati; Ananto A Alhasyimi (Wolters Kluwer Medknow Publications, 2018)
Introduction: To investigate the levels of human tumor necrosis factor-α (TNF-α) and transforming growth factor β1 (TGF-β1) in gingival crevicular fluid (GCF) during canine retraction movement using elastic chains and closed coil springs. Materials and Methods: One hundred patients (49 men and 51 women; mean age, 23.6 years) entering the space closure phase of fixed orthodontic treatment participated in this research. An upper canine of each patient was retracted using an elastic chain, and the contralateral canine was retracted using a closed coil spring. GCF samples were collected from the canine before and 7 days after the force was applied. human TNF-α and TGF-β1 were determined by enzyme-linked immunosorbent assay. Results: There were significant increase in the concentrations of both TNF-α and TGF-β1 at 7 days in both groups (P < 0.05). In the evaluation of between-group differences, significantly higher values were determined in the closed coil spring group. Conclusions: The results suggest that closed coil springs give higher TNF-α and TGF-β1 concentrations as compared to elastic chains, which make more bone remodeling to occur; therefore, closed coil springs can be considered as the treatment of choice for orthodontic canine retraction.